The effect of project-based learning on English writing skill for EFL learners - Taufik Arochman; Margana Margana; Ashadi Ashadi; Sarifah Achmad; Dwitiya Ari Nugrahaeni; Imam Baihaqi (Journal of Pedagogical Research, 2024)
Many EFL learners believe writing is a hard skill to master. Project-based learning is argued to be an effective solution to the problem. This study is aimed to look at the effect of Project-based learning (PJBL) on English writing skill for Indonesian EFL learners and their perceptions of PJBL. A mixed-method approach was implemented in this study. A pair sample t-test was used in analyzing the quantitative data of the written test while the descriptive-qualitative technique was applied in analyzing the data of the interview. Participants are thirty-nine tertiary students from Universitas Tidar. From the study, Indonesian EFL learners believe project-based learning influenced their writing skill in many ways. The result of this study is that there was a significant difference in project-based learning on English writing skill in pre and post-test for EFL learners which favor the improvement in grammar, vocabulary, organization, and content writing of the text. Project-based learning enhances the learners in linguistics aspects such as vocabulary knowledge, grammatical conventions, and punctuation. Besides, it also enhanced the learners' critical and creative thinking in the process of writing. In addition, project-based learning also motivated the learners to write as they were habituated to the independent learning situations that demand them to follow through all the processes accordingly: not to be left behind. Further studies are suggested to gain a deeper and broader comprehension of project-based learning's effect on student's writing skill.